2007
DOI: 10.1158/1055-9965.epi-07-0001
|View full text |Cite
|
Sign up to set email alerts
|

Path Analysis of Biomarkers of Exposure and Early Biological Effects among Coke-Oven Workers Exposed to Polycyclic Aromatic Hydrocarbons

Abstract: Many host factors or biomarkers are involved in the process of early DNA damage induced by occupational exposure to polycyclic aromatic hydrocarbons (PAH) as seen in coke-oven workers. This paper aimed to identify complicated causal interrelationship of various biomarkers using the path analysis. In this analysis, we included 235 subjects (166 cokeoven workers and 69 nonexposed controls) whose data on the comet assay (e.g., Olive tail moment) and cytogenetic analysis of peripheral blood lymphocytes as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
7
8
1
3
Order By: Relevance
“…The results of path analysis revealed that coke-oven exposure was the most influential factor for the levels of urinary 1-OHP and CBMN frequency, which was consistent with our previous findings (23). The XRCC1 Arg399Gln polymorphism is the most influential factor for DRC, which has a greater path coefficient than that of coke work.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of path analysis revealed that coke-oven exposure was the most influential factor for the levels of urinary 1-OHP and CBMN frequency, which was consistent with our previous findings (23). The XRCC1 Arg399Gln polymorphism is the most influential factor for DRC, which has a greater path coefficient than that of coke work.…”
Section: Discussionsupporting
confidence: 89%
“…The odds ratio and 95% confidence intervals (CI) were calculated to characterize the association between the coke-oven exposure and DRC using logistic regression with adjustment for age, and smoking and drinking status. The path analysis was used to identify the complicated causal interrelationship of various biomarkers (23). Path analysis is based on simple regression techniques, but it takes the researcher a step beyond the traditional regression analysis (24).…”
Section: Urinary 1-hydroxypyrene Level As An Internalmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, superior Ă s razĂ”es encontradas por Andrade e colaboradores para MP e HPAs. Isso pode ser explicado pelo fato de, na 10 fuligem, os HPAs ainda nĂŁo terem sofrido reaçÔes significativas de transformação em seus derivados, o que ocorre no material particulado atmosfĂ©rico [22].…”
Section: Resultsunclassified
“…Os HPAs constituem uma famĂ­lia de compostos caracterizada por possuĂ­rem 2 ou mais anĂ©is aromĂĄti-cos condensados [8,9]. VĂĄrios HPAs sĂŁ0 reconhecidos como agentes mutagĂȘnicos/carcinogĂȘnicos [10]. O pireno, um HPA de quatro anĂ©is condensados, ocorre em altas concentraçÔes na mistura de HPAs atmosfĂ©ri-co e Ă© absorvido pelo organismo vivo atravĂ©s da inalação, via oral ou em contato com a pele.…”
Section: Artigo Articleunclassified